Microhardness evaluation of root dentin after using resin sealer solvents - Gamze Nalci; Tayfun Alaçam; Bülent Altukaynak (Tabriz University of Medical Sciences, 2021)
Background. This study aimed to assess the effects of methyl ethyl ketone (MEK) and ethyl acetate (EA) on dentin microhardness, used as resin sealer solvents. Methods. Eighty halves of single-rooted teeth were randomly divided into four groups to apply MEK, EA, chloroform, or saline solution. Vickers hardness values were measured for three root levels before and after the direct application of solvents for 5 and 15 minutes or a 1-minute application with ultrasonic agitation. The results were analyzed using repeated-measures ANOVA, and adjustments were made for comparisons with Bonferroni tests. Results. The dentin microhardness decreased in all the solvent groups (P<0.05). The changes in microhardness increased with prolonged exposure times, except for the saline solution group. Chloroform exhibited the most significant decrease in value. Furthermore, ultrasonic agitation elicited a more substantial decline in values. Conclusion. MEK and EA might be preferred over chloroform as a solvent for resin sealers because they offer an attenuated decrease in dentin microhardness and do not have gutta-percha-dissolving properties.